Job Demand and Job Satisfaction in Latent Groups of Turnover Intention Among Licensed Nurses in Taiwan Nursing Homes. Issue 5 (25th May 2015) - Chen, I‐Hui; Brown, Roger; Bowers, Barbara J.; Chang, Wen‐Yin
Abstract: Nurses' turnover intention is not dichotomous; it may reflect intent to leave the profession, intent to leave a type of facility, or intent to leave a specific workplace. In a latent class analysis (LCA) of data from 186 licensed nurses (RNs and LPNs) recruited from 25 nursing homes (NHs) in Taiwan, we classified nurses into turnover intention subgroups based on seven questionnaire items and used a multilevel contrast analysis to characterize the subgroups according to demographic and facility factors, job demand, and job satisfaction. A multilevel probit model was used to examine how job demand and job satisfaction influenced subgroup membership. Three turnover subgroups were identified: high turnover intention (12%), middle turnover intention (57%), and low turnover intention (31%). The high turnover intention subgroup comprised the youngest nurses and had the lowest percentage of registered nurses (RNs); nurses in this subgroup had worked the longest at the current NH and had the greatest likelihood of working at a for‐profit facility. Nurses in the middle turnover intention subgroup had the lowest likelihood of working at a for‐profit facility. Nurses in the low turnover intention subgroup were primarily RNs and had the shortest work experience in the current facility. Nurses in the high and middle turnover intention subgroups reported lower intrinsic job satisfaction than those with low turnover intention. Extrinsic job satisfaction mediated the relationship between job demand and turnover intention subgroup assignment. The results of this LCA can help target interventions to address heterogeneity of turnover intention and ultimately lessen turnover. © 2015 Wiley Periodicals, Inc.